Cross-sections of photonuclear reactions on ⁿᵃᵗMo targets at end-point bremsstrahlung energy up to Eᵧₘₐₓ = 100 MeV - Vodin, A.N.; Deiev, O.S.; Timchenko, I.S.; Olejnik, S.M.; Kushnir, V.A.; Mytrochenko, V.V.; Perezhogin, S.O.; Bocharov, V.O. (Вопросы атомной науки и техники, 2021)
Experiments to determine the yields and bremsstrahlung flux-averaged cross-sections ⟨σ(Еγmax)⟩ of photonuclear reactions on the natural Mo targets were performed on the beam from the electron linear accelerator LUE-40 with the use of the γ-activation technique. The bremsstrahlung end-point energies were in the range Еγmax = 35…80 MeV. The bremsstrahlung quantum flux was calculated with the program GEANT4.9.2 and, in addition, was monitored using the ¹⁰⁰Мо(γ,n)⁹⁹Мо reaction. Calculations of the yields and average cross-sections ⟨σ(Еγmax)⟩ for photonuclear reactions on stable Mo isotopes were computed using the σ(Е) cross-sections from the TALYS1.95 code (for the level density model LD1). A comparison of experimental and calculated cross-sections ⟨σ(Еγmax)⟩ for reactions ⁹²Мо(γ, 2n)⁹⁰Мо and ⁹²Мо(γ, pn)⁹⁰Nb was performed Експерименти по визначенню виходів і перетинів фотоядерних реакцій на мішенях з натурального Мо виконані на пучку лінійного прискорювача електронів LUE-40 з використанням γ-активаційної методики. Область граничних енергій гальмівних γ-квантів становила Еγmax = 35…80 МеВ. Потік гальмівних квантів розраховувався в GEANT4.9.2 і додатково моніторувався по виходу реакції ¹⁰⁰Мо(γ, n)⁹⁹Мо. Розрахунки виходів і середніх перетинів ⟨σ(Еγmax)⟩ для фотоядерних реакцій на стабільних ізотопах Мо проводилися з використанням перетинів σ(Е) з коду TALYS1.95 (для моделі щільності рівнів LD1). Проведено порівняння експериментальних і розрахункових ⟨σ(Еγmax)⟩ для реакцій ⁹²Мо(γ, 2n)⁹⁰Мо, ⁹²Мо(γ, pn)⁹⁰Nb. Эксперименты по определению выходов и сечений фотоядерных реакций на мишенях из натурального Мо выполнены на пучке линейного ускорителя электронов LUE-40 с использованием γ-активационной методики. Область граничных энергий тормозных γ-квантов составляла Еγmax = 35…80 МэВ. Поток тормозных квантов рассчитывался в GEANT4.9.2 и дополнительно мониторировался по выходу реакции ¹⁰⁰Мо(γ, n)⁹⁹Мо. Расчеты выходов и средних сечений ⟨σ(Еγmax)⟩ для фотоядерных реакций на стабильных изотопах Мо проводились с использованием сечений σ(Е) из кода TALYS1.95 (для модели плотности уровней LD1). Проведено сравнение экспериментальных и расчетных значений ⟨σ(Еγmax)⟩ для реакций ⁹²Мо(γ, 2n)⁹⁰Мо, ⁹²Мо(γ, pn)⁹⁰Nb.